"Nunc antichristi multi facti sunt." - Idea společenství v Husově spisu "De ecclesia" - Šenovský, Jakub (Filosoﬁcký časopis, 2021)
This study explores the relationship between the metaphysical conception of the Church that can be found in Jan Hus’ treatise De ecclesia, and its possible social realization. The influences of this approach (Wycliffe and Augustine) are looked at, as are the problems that these influences bring with them. Hus’ conception of the church has broad social consequences, because Hus understands the church non-institutionally, i.e. as a collective organism of all who are predetermined for salvation. That is why, according to him, the Church is the pinnacle of all creation. If however we take this conception of the Church and the associated dualism between the Damned and the Church of the Chosen truly for what they are, and add in the eschatological expectation of the end of time and the coming of the Antichrist, then we might expect the revolutionary result of Hussitism. Lastly, the possible areas in which we can see Hus’ potential for broad social reform are shown.